2005
DOI: 10.1590/s0102-695x2005000100002
|View full text |Cite
|
Sign up to set email alerts
|

Análise do óleo essencial de folhas de três quimiotipos de Lippia alba (Mill.) N. E. Br. (Verbenaceae) cultivados em condições semelhantes

Abstract: INTRODUÇÃOLippia alba ocorre nas américas Central e do Sul, habitando praticamente todas as regiões do Brasil, onde é muito empregada como medicinal, pelas suas propriedades sedativa, carminativa, analgésica, espasmolítica e emenagoga (Zétola et al., 2002;Vale et al., 1999;Matos et al., 1996) Unitermos: Lippia alba, Verbenaceae, óleo essencial, citral, carvona, linalol.ABSTRACT: "Analysis of the essential oil from leaves of three Lippia alba (Mill.) N. E. Br. (Verbenaceae) chemotypes cultivated on the same con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
25

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 5 publications
2
42
1
25
Order By: Relevance
“…Citronellol (8) is a monoterpene found in some plants used in popular medicine with antihypertensive agents, including Cymbopogon citratus (Abegaz et al, 1983), Cymbopogon winterianus (Quintans-Júnior et al, 2008), and Lippia alba (Tavares et al, 2005). Bastos et al (2010) and showed that citronellol, administered intravenously, produced hypotension and tachycardia in conscious rats.…”
Section: Citronellolmentioning
confidence: 99%
“…Citronellol (8) is a monoterpene found in some plants used in popular medicine with antihypertensive agents, including Cymbopogon citratus (Abegaz et al, 1983), Cymbopogon winterianus (Quintans-Júnior et al, 2008), and Lippia alba (Tavares et al, 2005). Bastos et al (2010) and showed that citronellol, administered intravenously, produced hypotension and tachycardia in conscious rats.…”
Section: Citronellolmentioning
confidence: 99%
“…This can be attributed to the amount of metabolites present in the leaves, since different phenological stages of plants influence the amount and the dynamic of secondary metabolites that are present in them (GobboNeto and Lopes, 2007). Tavares et al (2005) analyzed the essential oil of three chemo types of Lippia alba and found an increase in the percentage of limonene during the flowering season, however the percentage of citral, carvone and linalool has slightly decreased during the reproductive phase. Németh et al (1993) have studied wild specimens of Achillea crithmifolia under different environmental conditions and developmental stages; they found that the rate of camphor in the essential oil decreased as the plants have advanced in their phenological stages.…”
Section: Resultsmentioning
confidence: 99%
“…A composição do óleo essencial de L. alba apresenta variação quantitativa e qualitativa, levando à separação em quimiotipos (Julião et al, 2003;Tavares et al, 2005 xylophilus (Park et al, 2007). De acordo com Matos (1996), o quimiotipo I é produtor de óleos essenciais ricos em mirceno, neural e geranial.…”
Section: Efeito Dos óLeos Essenciais Sobre Juvenis De Segundo Estádiounclassified